2018
DOI: 10.1161/circgen.117.001970
|View full text |Cite
|
Sign up to set email alerts
|

Hyperacute Monocyte Gene Response Patterns Are Associated With Lower Extremity Vein Bypass Graft Failure

Abstract: Background Despite being the definitive treatment for lower extremity peripheral arterial disease, vein bypass grafts fail in half of all cases. Early repair mechanisms following implantation, governed largely by the immune environment, contribute significantly to long-term outcomes. The current study investigates the early response patterns of circulating monocytes as a determinant of graft outcome. Methods and Results In 48 patients undergoing infrainguinal vein bypass grafting, the transcriptomes of circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 48 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…The expression of STAT3 or MYD88 predicted a clinically significant stenosis or thrombosis of the VG within the following year [70]. In these clusters of genes, DICER1 (a regulator gene of RNA silencing via miRNAs) was also identified [70]. Regulation of miRNAs is observed in remodeling and VGF, but needs further detailed investigation [50].…”
Section: Monocytesmentioning
confidence: 99%
“…The expression of STAT3 or MYD88 predicted a clinically significant stenosis or thrombosis of the VG within the following year [70]. In these clusters of genes, DICER1 (a regulator gene of RNA silencing via miRNAs) was also identified [70]. Regulation of miRNAs is observed in remodeling and VGF, but needs further detailed investigation [50].…”
Section: Monocytesmentioning
confidence: 99%
“…Rehfuss et al 27 reported a genomic study of infrainguinal vein bypass grafting involving 48 patients, among whom 35 succeeded and 13 failed. To investigate the genomic mechanism underlying graft outcome, transcriptomes of circulating monocytes from patients of success and failure were monitored at pre-operation and at days 1, 7, and 28 post-operation.…”
Section: Resultsmentioning
confidence: 99%
“…We validated the utility of our approach by analyzing gene expression data from surgical patients. Vein bypass grafting is an essential treatment for lower extremity arterial occlusive disease, but only with 30 – 50% success rate 27 . The biological mechanisms underlying the outcome of grafts include cue-induced differentiation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We test and validate the framework by analyzing genomic data of circulating monocytes from human infrainguinal vein bypass grafting, aimed at treating lower extremity arterial occlusive disease. 28 The utility of the framework is also supported by a second vein graft experiment for rabbits. 29 By reconstructing graft- and outcome-perturbed idopNetworks, we can potentially gain a mechanistic understanding of vein bypass graft success vs. failure.…”
Section: Introductionmentioning
confidence: 89%